Dépendance, attachement, contestation : quelles transitions pour les stations de sports d’hiver ? - Émeline Hatt; Cécilia Claeys (Revue de Géographie Alpine, 2024)
In light of the increasing urgency of transition, this article examines strategies for transition in relation to ski resorts. It focuses on both official transition initiatives (support for resorts by regional authorities) and citizen-driven initiatives (associations and local residents). The study, which focuses on Alpine resorts in the south of France, highlights the emergence of institutional and group initiatives aimed at ecological transition, while identifying some of the obstacles to the evolution of the socio-technical system of winter sports. Our findings clearly show economic dependency and a socio-political attachment to the alpine ski resort model among both institutional actors and residents, especially secondary residents